Diseño y construcción de un biodigestor tipo campana flotante con la utilización de desechos porcinos para la finca "El Recuerdo" - Báez Cazares, Gabriel Esteban (2015)
The main objective of this project was to create a clean energy source that takes advantage of the waste of pigs generated in the farm "El Recuerdo". Allowing to the citizens to stop depending on electricity or LPG to cook their meals. Also as a result of the investigation, it was found that the decomposed side or biol is a powerfull sourace of nutrients that will be used in plantations. There are several methods used in the deployment of this project, with the scientific method it was possible to deepen the analysis of biogas generating process from pig waste, this biological process is developed in the absence of oxygen, which results in the generation of methane and carbonic gas, this work it is made mainly by bacterial colonies. Biodigesters can help to satisfy any energy requirement, the sizing is done to optimize the management of the organic waste available, through the analytical or mathematical method the capacity of the digestion chamber tank will be determined, as well as the storage which is 1100 liters each, based on the amount of pig waste produced daily in the farm and the amount of biogas produced in the anaerobic process. The parameters analyzed with the previous methods determine the technical method in which the design and construction of the digester will be made, with the main elements that compose it and with the ending of the project, which will promote the strengthening of renewable energies in rural areas.